Development of a pH-responsive pegylated chitosan nanocarrier for targeted delivery of 17-AAG and synergistic therapy in HER2+ breast cancer - Samira Alipour; Mahmoud Reza Aghamaali; Atiyeh Mahdavi (Scientific Reports, 2025)
Abstract A pH-responsive PEGylated chitosan nanocarrier was developed for the targeted delivery of 17-(Allylamino)-17-demethoxygeldanamycin (17-AAG) to HER2 + breast cancer cells. The nanoparticle formulation was prepared using ionic gelation with sodium tripolyphosphate (TPP), followed by post-loading of 17-AAG. The resulting nanoparticles exhibited a spherical morphology, an average size of ~ 152 nm, and a positive zeta potential (+ 28.60 mV). Drug encapsulation efficiency reached 80%, with sustained release under acidic conditions (pH 5.50), mimicking the tumor microenvironment. In vitro cytotoxicity assays demonstrated a significant enhancement in potency, with an IC 50 of 2.30 µM after 72 h, representing a threefold increase compared to free 17-AAG. The nanoformulation induced G2/M cell cycle arrest and apoptosis in T47D cells. qRT-PCR analysis revealed a 72.10% downregulation of HSP90 mRNA, indicating effective intracellular delivery and target engagement. Furthermore, combination with trastuzumab showed synergistic effects, suggesting disruption of the HER2 signaling pathway. These findings highlight the potential of this nanoplatform as a strategy with therapeutic potential for improving the therapeutic efficacy of 17-AAG in HER2 + breast cancer.